USING ALUMINUM REFUSE AS A COAGULANT IN THE COAGULATION AND FLIOCCULATION PROCESSES - Ferhood Makki, Hasan; Faiq Al-Alawy, Ahmed; N. Abdul-Razaq, Nada; Adnan Mohammed, Manal (Iraqi Journal of Chemical and Petroleum Engineering, 2010)
The present work aims to study the efficiency of using aluminum refuse, which is available locally (after dissolving it in sodium hydroxide), with different coagulants like alum [Al2 (SO4)3.18H2O], Ferric chloride FeCl3 and polyaluminum chloride (PACl) to improve the quality of water. The results showed that using this coagulant in the flocculation process gave high results in the removal of turbidity as well as improving the quality of water by precipitating a great deal of ions causing hardness. From the experimental results of the Jar test, the optimum alum dosages are (25, 50 and 70 ppm), ferric chloride dosages are (15, 40 and 60 ppm) and polyaluminum chloride dosages were (10, 35 and 55 ppm) for initial water turbidity (100, 500 and 1000 NTU) respectively. While, adding sodium aluminate with the coagulants (Alum, FeCl3 and PACl), the optimum dose of 50 ppm was enough for the reduction of turbidity and hardness of water.